Making Equity a "Reality": Structural Violence, Community-Engaged Scholarship, and Social Transformation - Kimberly L. King-Jupiter (The University of Alabama, 2022)
This is an essay by Dr. Kimberly L. King-Jupiter, guest editor of a forthcoming special issue of JCES. Set to be published in 2020, this special issue shines a spotlight on the research conducted predominantly at historically black colleges and universities (HBCUs) and other minority-serving institutions (MSIs), as well as on these institutions' immense contributions to the communities they serve and the disciplines they represent. Dr. King-Jupiter's essay is an excellent framing piece for the two research articles that follow, both providing a preview of the kind and quality of research you will find in the special HBCU issue. We believe these articles will stimulate your interest in learning more about the critical role these important institutions play in their communities and in our society.